Knowledge, attitude and behaviour of Malaysian female adolescent smokers - Nik Mohamed, Mohamad Haniki; Mohamad Noor, Zaswiza; Kaur, Swinder Jit; Abu Bakar, Salehuddin (Medknow Publications, 2010)
Background: Smoking among Malaysian female 13 to 18 years is 4.8% (NHMS 2, 1996). However, assessment of knowledge and perception regarding smoking in this group is lacking. Objectives: To determine smoking-related knowledge, attitude and behaviour among female adolescent smokers. Methods: 56 female adolescent smokers selected randomly at a shopping mall were given questionnaires to self-administer upon consent. Questionnaires contain demographic data and 30 smoking-related questions. Results: Mean age is 17.85 ± 1.1 (range 16 to 19) years. Of 56 girls, 40% smoked everyday. 32% of the subjects smoked more than 20 sticks, 50% smoked 2-20 sticks and 18% smoked less than 2 sticks per day. 78% bought cigarettes from convenient stores or restaurants. 66% smoked at public area and 62.5% smoked without family acknowledgement. 18% also tried shisha, bidis, cigars and chewing tobacco. 21.4% will still smoke in the next 5 years. 69.6% agreed that quitting is difficult. 71.4% agreed smoking makes appearance less attractive. Only 23.2% thought smoking makes one become more outstanding. 55.4% disagreed that smoking reduces their weight vs. 42.9% who agreed. 91.1% realized inhaling other person’s tobacco smoke is harmful. Only 23.2% admitted that smoking is wasteful. 87.5% agreed with the ‘No Smoking’ signs at the public places. 60.7% wanted to quit smoking if possible. Conclusion: Smoking among female adolescents in Malaysia is a serious problem. Adolescent smokers need to be educated further regarding the harmfulness of smoking and provided assistance with quitting.